SO070THE SPECTRUM OF RENAL OSTEODYSTROPHY IN PREVALENT PERITONEAL DIALYSIS PATIENTS IN 21ST CENTURY - A HISTOMORPHOMETRIC ANALYSIS OF BONE BIOPSIES. (6th June 2020) - Pereira, Luciano; Magalhães, Juliana; Mendonça, Luís; Diniz, Hugo; Sousa, Maria João; Neto, Ricardo; Carvalho, Catarina; Oliveira, Ana; Beco, Ana; Frazao, Joao M
Abstract: Background and Aims: The spectrum of renal osteodystrophy (ROD) in peritoneal dialysis (PD) patients remains to be clarified. Most studies are old and the results inconsistent. Also there were changes in clinical practice that may have influenced the bone histology in PD patients. Method: In order to characterize ROD in prevalent PD population, we performed tetracycline-labelled bone biopsies in 49 PD patients with histomorphometric analysis according KDIGO guidelines. Exclusion criteria: history of kidney transplant, hemodialysis, treatment with agents interfering in bone metabolism (for example bisphosphonates). Hands and pelvis x-ray were performed to evaluate vascular calcification (VC) and to calculate the Adragão score. All patients were treated with biocompatible PD solutions, with calcium concentration of 1.25 mmol/L. Results: Forty-nine patients participated in the study, with 32 biopsies analyzed so far. Mean age was 52.4±10.9 years, 16 male, 6 with diabetes mellitus, 23 on manual PD, median time on PD was 22.1 (3-61) months. Mean calcium, phosphate and PTH were 9.2±0.5 mg/dL, 4.9±1.0 mg/dL and 489.87±227.8 pg/mL, respectively. Vascular calcification was detected in 29% of patients and mean Adragão score was 1.13. Essential histomorphometric and selected data is represented in table 1: Bone volume (BV) tended to be lower in diabetics - 17.1% (10.1-23.1) compared with non-diabetics – 22.6% (12.7-41.4) (p=0.07). Median bone formation rate (BFR) tended to be lower - 21.39 µm 3 /µm 2 /y (8.2-53.2) in diabetic patients than in non-diabetics - 28.63 µm 3 /µm 2 /y (3.5-89.77) (p=0.80). PTH levels also tended to be lower in diabetics – 384.8 pg/mL compared to non-diabetics – 514.1 pg/mL (p=0.14). BV tended to be lower in patients with VC – 19.1% (10.1-27) compared with patients without VC - 22.6% (12.7-41.4) (p=0.23). VC was detected on x-ray in all 6 patients with diabetes and only in 11.5% (3 in 26) of non-diabetic patients. Conclusion: Similar to previous reports, the most frequent ROD pattern was ABD. However, PD patients with ABD had mean PTH of 405 pg/mL, a value well within the recommended KDIGO targets. This reinforces PTH as a far from ideal marker of bone turnover and suggests different targets for PTH levels in this seemingly highly susceptible population to ABD even when treated with low calcium dialysate. The proportion of patients with normal bone was higher than previously published. This finding can be explained by differences in the classification of ROD and prescription of biocompatible PD solutions in all patients. Diabetic patients tended to have lower BV and BFR. This finding is not surprising considering osteoblastic toxicity caused by advanced glycation end products. Also diabetic patients have a state of relative hypoparathyroidism. In conclusion, the most frequent pattern was ABD. Diabetic patients on PD may be a different subgroup.